2014
DOI: 10.3390/mi5030766
|View full text |Cite
|
Sign up to set email alerts
|

SU-8 Photolithography as a Toolbox for Carbon MEMS

Abstract: Abstract:The use of SU-8 as precursor for glass-like carbon, or glassy carbon, is presented here. SU-8 carbonizes when subject to high temperature under inert atmosphere. Although epoxy-based precursors can be patterned in a variety of ways, photolithography is chosen due to its resolution and reproducibility. Here, a number of improvements to traditional photolithography are introduced to increase the versatility of the process. The shrinkage of SU-8 during carbonization is then detailed as one of the guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 70 publications
2
75
0
Order By: Relevance
“…Results are shown in figure 2. Similar to results obtained by other authors (13), it was observed that the shrinkage in height for tall posts is less than that seen with shorter posts of the same cross section. In order to analyze shrinkage, the % shrinkage in height and diameter, as calculated using equation 1, was plotted against the aspect ratio of the original SU-8 post ( fig.…”
Section: Resultssupporting
confidence: 90%
“…Results are shown in figure 2. Similar to results obtained by other authors (13), it was observed that the shrinkage in height for tall posts is less than that seen with shorter posts of the same cross section. In order to analyze shrinkage, the % shrinkage in height and diameter, as calculated using equation 1, was plotted against the aspect ratio of the original SU-8 post ( fig.…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure 6c, few bright spots were observed in the magnified fluorescent microscope after photolithography. In addition, pattern uniformity (e.g., thickness, a line‐edge roughness, and a line‐width roughness) is also very important for the fabrication of microelectronic systems 37. As shown in Figure 6d,e, scanning electron microscope (SEM) also exhibited the good pattern clearance.…”
Section: Introductionmentioning
confidence: 94%
“…Alternatively, low toxic solvents (e.g., ethanol)25 have been introduced but are impractical due to the low flash point. In addition, severe QD aggregation4,13,16,26–29 during dispersion and micro‐patterning30–35 is the next notable problem, which is caused by the incompatibility between the surface ligand and binders such as polymers, reactive monomers/oligomers, and functional additives in the photopolymerizable mixtures 36–39…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the development of carbon thin‐film electrochemical platforms is scarce and has been kept going. The ones developed so far are mainly produced by photolithographic patterning and subsequent carbonization of photoresists like SU‐8 . However, the stability of these devices is compromised by the weak interfacial adhesion to the substrate, which is manifested by film flaking during immersion in the different solvents required for film processing and operation of the resulting electrochemical devices.…”
Section: Electroanalytical Devices Made With Resorcinol‐formaldehyde mentioning
confidence: 99%